ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI EARNINGS RESPONSE COEFFICIENT (ERC) (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2010-2014) - Yuni Susianti, 12.05.52.0044; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2016)
In the decision-making , investors do not just look at the stock price increase is positive, but can use other information that may be used as consideration of decision making, this is because the information may be biased means earnings information occurs because of inaccuracies and their management practices reporting the company's financial profit. The purpose of this study to determine how the effects of capital structure (leverage), the systematic risk, growth opportunities, company size, and profitabiilitas against earnings response coefficient. Research was conducted on Manufacturing Companies listed on the Stock Exchange in 2010-2014 with a purposive sampling techniques was obtained total sample of 155 companies. The analysis technique used is multiple regression analysis. These results indicate the capital structure (leverage), the systematic risk significant negative effect, systematic risks and growth opportunities significant positive effect, while the size and profitability was not significant positive effect.Keywords: Capital Structure (Leverage), Systematic Risk, Growth Opportunities, Company Size, Profitability, Earnings Response Coefficient